Governance of Village Owned Enterprise from The Perspective of Reinventing Government - Faradillah Hasan; Rizal Yaya (Universitas Muhammadiyah Surakarta, 2019)
Act No Year 2014 on Village Government contains regulations concerning village decentralization to carry out villages development in accordance with their respective potential. Based on these regulations, each village has a big role in achieving village development goals. Therefore the establishment of BUM Desa is the right way to build a tradition of democracy in the village to achieve a higher economic degree of rural communities in achieving prosperity for the village community. The main idea in this thesis is how the public sector, especially the BUM Desa of the Tirta Mandiri, Ponggok Village, run its institutions more competitively, effectively and efficiently through the ten principles of Reinventing Government. This thesis uses an exploratory qualitative approach. Provided by several informants, including the Finance Chief, Secretary and Person in charge of BUM Tirta Mandiri Village and the Ponggok Village Community. Data collection techniques conducted by the researcher are interviews, observation and literature review. Data analysis method used is a descriptive method. The collected data is then analyzed using the interactive analysis method of Miles and Huberman which consists of four stages. Based on the results of this thesis, it was found that the 10 principles initiated by Osborne and Gaebler underlie the success in the management of BUM Desa Tirta Mandiri in Ponggok Village, Klaten, Central Java